2006
DOI: 10.1093/ajcn/84.4.835
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial metabolic fate of tocotrienol-rich vitamin E differs significantly from that of α-tocopherol

Abstract: Tocotrienols are detected in postprandial plasma, albeit in significantly lower concentrations than is alpha-tocopherol. This finding confirms previous observations that, in the fasted state, tocotrienols are not detected in plasma. Tocotrienol transport in lipoproteins appears to follow complex biochemically mediated pathways within the lipoprotein cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 37 publications
6
62
0
4
Order By: Relevance
“…In an animal study, it was shown that enterocytes use two pathways for vitamin E absorption and that the major pathway of a-tocopherol absorption is via chylomicrons (42). Furthermore, in a human study with fat-rich meal feeding, a-tocopherol in LDL and HDL decreased postprandially, concomitantly with a rise in triglyceride-rich lipoprotein a-tocopherol in healthy subjects (43), and plasma concentration of a-tocopherol was reported to be increased at 2 h after supplementation (44). These reports support the difference of a-tocopherol/lipid concentration at 120 min after the BB meal and after the BBS meal in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In an animal study, it was shown that enterocytes use two pathways for vitamin E absorption and that the major pathway of a-tocopherol absorption is via chylomicrons (42). Furthermore, in a human study with fat-rich meal feeding, a-tocopherol in LDL and HDL decreased postprandially, concomitantly with a rise in triglyceride-rich lipoprotein a-tocopherol in healthy subjects (43), and plasma concentration of a-tocopherol was reported to be increased at 2 h after supplementation (44). These reports support the difference of a-tocopherol/lipid concentration at 120 min after the BB meal and after the BBS meal in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, intake of anti-oxidative supplements such as a-tocopherol is reported to have a greater effect on oxidative stress in subjects with postprandial state abnormalities such as hyperglycemia and hyperlipidemia (10). However, the amounts of purified dietary fiber and antioxidant vitamins that have been studied were much larger than the usual intakes from one meal (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…This is the first investigation to focus on the effects of vegetable consumption on changes in postprandial PON1 levels. The consumption of vegetables 22,23) or meals supplemented with vitamins 24,25) reportedly increases the amount of lipid soluble antioxidants in postprandial TG-rich lipoproteins. Therefore, colored vegetable consumption is expected to decrease postprandial oxidative stress and increase PON1 activity by protecting PON1 enzymes from oxidative stress-induced inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several acute studies with oral supplementation of palm T3 in a single dose from 200 mg to 1011 mg did not report any acute adverse event (Yap et al, 2001;Yap and Yuen, 2004;Fairus et al, 2006). Also in chronic studies, long-term supplementation of T3 ranging from one month to five years did not report any events of discomfort or toxicities in the subjects investigated (Tomeo et al, 1995;Qureshi et al, 1997;Mensink et al, 1999;Nesaretnam et al, 2010;Zaiden et al, 2010;Mahalingam et al, 2011;Yuen et al, 2011;Heng et al, 2013).…”
Section: Ramdomised (N=32) (16 Males and 16 Females)mentioning
confidence: 99%